Technology Teaching Media System of Pneumatic and Automation for Engineers - Villacres Cevallos, Edison (2017)
The rapid advancement of science and technology has facilitated the automation of production processes, encouraging the industry to demand professionals with solid technical knowledge in this area. This paper presents a system of technological means for teaching and skills development in the area of pneumatic and automation. The media system consists of three phases categorized into themes, each of which uses design and simulation software, training and support teams in virtual learning environments, which guide the student from basic knowledge of the principle of pneumatics to the development of automated processes. This system of technological teaching aids based on the action, experience, work groups and practical applications which means learning by doing. As a result, it has improved the interest and motivation of students to the pneumatics and the formation of skills that will facilitate their integration into the labor market in this important area of industry.